Defoe's footprints : essays in honour of Maximillian E. Novak - Maniquis, Robert M.; Fisher, Carl, 1958-; Novak, Maximillian E.; William Andrews Clark Memorial Library; University of California, Los Angeles. Center for 17th- & 18th- Century Studies (Toronto [Ont.] : Published by the University of Toronto Press in association with the UCLA Center for Seventeenth- and Eighteenth-Century Studies and the William Andrews Clark Memorial Library, 2009)
With attention to Defoe's neglected writings as well as to his important works, this volume uncovers his distance from and influence on modern literature, paying tribute to Maximillian E. Novak by presenting new ideas about, and new readings of, Daniel Defoe.
Introduction / Robert M. Maniquis and Carl Fisher -- Defoe's silences / Stuart Sherman -- The atmospheres of Robinson Crusoe / Jayne Lewis -- Poetic footprints : some formal issues in Defoe's verse / J. Paul Hunter -- Mimesis/mimesis and the eighteenth-century British novel: representation and knowledge/ John Richetti -- Robinson Crusoe and the semiotic crisis of the eighteenth century / Robert Folkenflik -- Powerful affections : slaves, servants, and labours of love in Defoe's writing / Roxann Wheeler -- Defoe's "Black Prince" : elitism, capitalism, and cultural difference / Laura Brown -- "The project and the people" : Defoe on the South Sea bubble and the public good / Carl Fisher -- The writer as hero from Jonson to Fielding / Manuel Schonhorn -- Robinson Trousseau : Joyce's Defoe / Michael Seidel -- The novel as modern myth / John Bender.
"Maximilian E. Novak: a bibliography" (p. [239]-249).
Includes bibliographical references and index.
Print version record.
English.
JSTOR
Keywords: Defoe, Daniel, -- 1661?-1731 -- Criticism and interpretation; Defoe, Daniel, -- 1661?-1731; LITERARY CRITICISM -- European -- English, Irish, Scottish, Welsh; Literary criticism; Festschriften; Criticism, interpretation, etc; Festschriften; Literary criticism; Critiques littéraires.